DIMENSIONAL ACCURACY OF ULTRASONIC ASSISTED FUSED DEPOSITION MODELING SYSTEM PRINTED SPECIMEN - Maidin, S.; Iryani, N.I.; Ting, K.H.; Pei, E. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Studies on the effects of ultrasonic vibration on the dimensional accuracy and surface roughness of machined specimen have been conducted extensively. However, the effects of ultrasonic vibration on the dimensional accuracy of FDM specimen has never been recorded. This study investigates the effect of various frequencies of ultrasonic vibration on the dimensional accuracy of 3D printed specimens. An open-source FDM printer integrated with an ultrasonic piezoelectric transducer was used to print the test specimens. The frequency was set at 0 kHz, 7 kHz, 15 kHz, and 20 kHz to print ABS and PLA filament material. The printed specimens’ dimensional accuracy was tested using a coordinate measuring machine. Parameters such as the length, width, height, thickness, corner radius, angularity, and perpendicularity were checked. Frequency set to 20 kHz results in drastic improvement of dimensional accuracy for PLA specimen. In contrast, for the ABS specimens, the ultrasound frequency (7 kHz and 15 kHz) affect and improved only the thickness accuracy. However, all other geometries failed to meet the expected dimensional accuracy. The application of ultrasound does not result in any significant changes in the dimensional accuracy of the 3D printed specimens in ABS material.